Identification of a Prognostic Signature Based on Tumor-Infiltrating B Lymphocyte mRNA in Head and Neck Squamous Cell Carcinoma - Mingjun Zhang; Qi Sun; Yisong Yao; Xi Chen; Jiaxuan Li; Ting Yuan; Yakui Mou; Yumei Li; Xicheng Song (Journal of Immunology Research)
Discussion: This study provides risk assessment and outcome prediction for patients with HNSCC and provides potential targets for immunotherapy of HNSCC.